The African Women Theologians contribution towards the discussion about alternative masculinities - Dube, Zorodzai (Verbum et ecclesia, 2016)
In a celebratory mood because of the unparalleled, heroine works of the Circle of Concerned African Female Theologians, from hereon the CIRCLE, I pose to assess their use of critical tools such as alternative masculinities. Largely, the CIRCLE writers engaged with the concept of alternative masculinity from the perspective of Christology, associating Jesus with motherlike virtues of caring and loving, which also became the basis to critique African hegemonic masculinities and patriarchy. While success has been achieved from a cultural perspective, in this study I suggest that emphasis should be diverted towards exploring strategies that empower women economically.Intradisciplinary and/orinterdisciplinary implications: The study uses theories from cultural studies, critical theory, and contextual and gender studies to locate the voices of African women theologians in their discussion of Alternative masculinity. By using contextual Christologies based on the African woman s experience, the study adds to knowledge concerning the discussion of gender and alternative masculinities, in the process, highlighting the voices of African women theologians to the discussion.Keywords: Alternative masculinities; racial stereotypes; capitalism; socialisation